Distributive politics inside the city? The political economy of Spain's plan E - Felipe Carozzi; Luca Repetto (Uppsala University, Department of Economics, 2016)
We study the allocation of investment projects by municipal governments across groups of voters using data from a fiscal stimulus program carried out in Spain between 2009 and 2011. This program provided municipalities with a large endowment to spend in public investments and required the geocoding of each individual project. Combining these data with disaggregated election information at the census area level, we study whether politicians use expenditures to target their supporters or to raise turnout. Estimates from regression, matching and RDD methods show no evidence of local governments targeting areas of core support. Instead, investment goes disproportionately to low turnout areas, suggesting that politicians use funds to increase participation. We confirm this hypothesis by showing that, in the following elections, turnout is increased in areas that received more investment. Our results suggest that mobilization can be a strong force in shaping the allocation of resources across voter groups within cities.
urn:nbn:se:uu:diva-310886
Keywords: R53; H76; D72; 330; Political economy; Distributive Politics; Core voters; Turnout; Partisan alignment